2000
DOI: 10.1007/s003300050083
|View full text |Cite
|
Sign up to set email alerts
|

Image-guided percutaneous drainage of thoracic empyema: Can sonography predict the outcome?

Abstract: The aim of this study was to assess the safety and efficacy of image-guided percutaneous catheter drainage (IGPCD) of thoracic empyemas, and to correlate the outcome of IGPCD with the pre-procedural sonographic appearance. One hundred three patients (74 males and 29 females) with thoracic empyema (age range 1 month to 70 years, median age 28 years) underwent IGPCD. In 63 (61.17%) patients, IGPCD was the primary treatment modality; in 40 (38.84%) patients it was used after unsuccessful intercostal chest tube dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0
5

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(48 citation statements)
references
References 13 publications
3
40
0
5
Order By: Relevance
“…22 In our study ultrasonographic findings did not affect outcome and this differs from a report of image guided percutaneous drainage without the use of a fibrinolytic agent. 23 Furthermore, a recent report on the role of CT scanning and ultrasound in adult patients concluded that neither technique could reliably identify the stage of pleural infection or predict those who required surgical intervention. 24 Some differences were found between the groups at trial entry.…”
Section: Discussionmentioning
confidence: 99%
“…22 In our study ultrasonographic findings did not affect outcome and this differs from a report of image guided percutaneous drainage without the use of a fibrinolytic agent. 23 Furthermore, a recent report on the role of CT scanning and ultrasound in adult patients concluded that neither technique could reliably identify the stage of pleural infection or predict those who required surgical intervention. 24 Some differences were found between the groups at trial entry.…”
Section: Discussionmentioning
confidence: 99%
“…These tubes are better tolerated than large bore (20-24 F) intercostal drains [25]. Some prospective studies have found that 8-12 F pigtail catheters or 10-14 F catheters inserted under ultrasonographic guidance are at least as effective as larger catheters [26][27][28].…”
Section: Pleural Pathology Pleural Effusionsmentioning
confidence: 99%
“…Buzdolabında bekletildiğinde S. pneumoniae, H. influenzae ve anaerobların üremesi inhibe olmaktadır. Plevra sıvısı pH, glukoz ve LDH düzeyleri tedavi yönteminin seçiminde ve tedaviye yanıtın değerlendiril-mesinde öncelikle gereklidir (16)(17)(18).…”
Section: Taniunclassified